1999
DOI: 10.1017/s0022112099004280
|View full text |Cite
|
Sign up to set email alerts
|

Direct numerical simulation of turbulent flows with cloud-like off-source heating

Abstract: Direct numerical solutions of the incompressible Navier–Stokes equations have been obtained under the Boussinesq approximation for the temporal evolution of a turbulent jet-like flow subjected to off-source volumetric heating, of the kind that occurs in a cloud due to latent heat release on condensation of water vapour. The results show good qualitative agreement with available experimental data on spatially growing jets. Thus, heating accelerates the flow and arrests jet growth; and turbulence veloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 19 publications
5
36
0
Order By: Relevance
“…Qualitatively similar behavior is observed in the present experiments on steady diabatic flows, in which rough estimates of the turbulent mixing time scale indicate that it decreases approximately by a factor of two (from 1.5 s to 0.7 s) with height over the extent of the HIZ (for details on the estimates of τ mix see SI Text, section 6 and Table S2). This is consistent with lower dilution due to the distortion [owing to axial acceleration (47,51)] and disruption of coherent structures (10,48), accompanied by faster mixing due to intensification of small-scale vorticity caused by the baroclinic torque (48), both resulting from off-source diabatic heating. These physical effects make conditions favorable for more homogeneous mixing as we move up beyond cloud base.…”
Section: Implications Of Laboratory Cloud Simulationssupporting
confidence: 75%
“…Qualitatively similar behavior is observed in the present experiments on steady diabatic flows, in which rough estimates of the turbulent mixing time scale indicate that it decreases approximately by a factor of two (from 1.5 s to 0.7 s) with height over the extent of the HIZ (for details on the estimates of τ mix see SI Text, section 6 and Table S2). This is consistent with lower dilution due to the distortion [owing to axial acceleration (47,51)] and disruption of coherent structures (10,48), accompanied by faster mixing due to intensification of small-scale vorticity caused by the baroclinic torque (48), both resulting from off-source diabatic heating. These physical effects make conditions favorable for more homogeneous mixing as we move up beyond cloud base.…”
Section: Implications Of Laboratory Cloud Simulationssupporting
confidence: 75%
“…Elavarasan et al, 1995;Bhat and Narasimha, 1996; and numerical simulations (e.g. Basu and Narasimha, 1999;. Here, additional energy is injected into a welldeveloped jet far from the source and over a finite streamwise extent.…”
Section: Mechanisms For Entrainment In Cloudsmentioning
confidence: 99%
“…Specifically, [5,6] had reported a decrease in their normalized fluctuations, whereas the experimental findings in [3] have indicated that the normalized rms for streamwise velocity increases. The present computations, albeit at a higher heating rate, suggest a complex behavior of the rms fluctuations for the streamwise velocity within the HIZ that possibly contributed to the contradictory results reported earlier.…”
Section: Profiles Of Fluctuating Quantitiesmentioning
confidence: 99%
“…Such a three-way coupling of the momentum, scalar and energy equations has not been attempted by previous DNS investigations of heated jets. For example, Basu and Narasimha [5] did not solve for the scalar field and instead used a time-averaged heat injection profile in their computations.…”
Section: Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation